The Effectiveness of MURDER Cooperative Model towards Students' Mathematics Reasoning Ability and Self Concept of Ten Grade - Prasetiyo, Sofan Tri; Dwijanto, Dwijanto; Sunarmi, Sunarmi (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was to know the effectiveness of MURDER cooperative model towards students’ mathematics reasoning ability and self concept of ten grade. Population of this research were students of MIA ten grade Senior High School 1 Kebumen in the academic year 2016/1017. Sampling technique using simple random sampling technique. The data collected by the method of documentation, test methods, observation methods, and questionnaire methods. The analyzed of data are used completeness test and average different test. The results showed that: (1) mathematics reasoning ability of students that following MURDER cooperative model have completed individual and classical study completeness; (2) mathematics reasoning ability of students that following MURDER cooperative model better than mathematics reasoning ability of students that following ekspository learning; (3) self concept of students that following MURDER cooperative model better than self concept of students that following ekspository learning.